Vertical Variations of Cloud Microphysical Relationships in Marine Stratocumulus Clouds Observed During the ACE‐ENA Campaign. Issue 24 (13th December 2021) - Yeom, Jae Min; Yum, Seong Soo; Shaw, Raymond A.; La, Inyeob; Wang, Jian; Lu, Chunsong; Liu, Yangang; Mei, Fan; Schmid, Beat; Matthews, Alyssa
Abstract: This study examines the vertical variations of cloud microphysical relationships and their implications to cloud microphysical processes in marine stratocumulus clouds using in‐situ aircraft observations during the Aerosol and Cloud Experiments in Eastern North Atlantic (ACE‐ENA) field campaign. A new diagram with a coordinate system based on cloud droplet liquid water content (Lc ) and phase relaxation time scale is proposed to investigate mixing mechanisms. This new diagram analysis shows that the inhomogeneous mixing trait is dominant near the cloud top, but homogeneous mixing trait is stronger at lower altitudes. The relevant scale parameters (i.e., transition length scale and transition scale number) also indicate a high likelihood of inhomogeneous mixing. The relationship between Lc and standard deviation of droplet radius (σR ) clearly shows the vertical transition: the correlation between Lc and σR is positive at lower cloud altitudes, but it becomes negative as altitude increases. Such a vertical transition is consistent with the vertical circulation mixing, modulating the cloud microphysical relationships to suggest homogeneous mixing at a significant depth from the cloud top. Plain Language Summary: Stratocumulus (Sc) clouds are climatically crucial as they cover large regions of Earth's surface and influence the radiative balance of the Earth. For these clouds, entrainment‐mixing of the air from above cloud top has been considered as one of the most important processes that modulates the relationships among cloud microphysical parameters. We investigate marine stratocumulus clouds observed at various altitudes. We propose a new mixing diagram based on the liquid water content and the phase relaxation time. Cloud microphysical relationships analyzed in this coordinate system suggest inhomogeneous mixing near cloud top, becoming more consistent with the character of homogeneous mixing at lower cloud altitudes. Such vertical variation of mixing signature is consistent with the vertical circulation hypothesis. Key Points: A new mixing diagram is proposed to analyze cloud microphysical relationships Analysis shows a transition of cloud microphysical relationships with cloud altitude Vertical circulation mixing is suggested to explain a vertical variation of cloud microphysics